![\small{Hlo frndz} \small{Hlo frndz}](https://tex.z-dn.net/?f=%5Csmall%7BHlo+frndz%7D)
D is a point on side BC of triangle ABC such that AD=AC.Show that AB>AD.
Answers
Answered by
17
Given,
AD = AC
We know,
Angles opposite to equal sides are equal,
We get,
Angle (ACD) = Angle (ADC)
Again, we know,
Angle (ADC) is an exterior angle for triangle (ABD),
Exterior angle = sum of opposite interior angles
So,
Angle(ADC) = Angle(ABD) + Angle(BAD)... (1)
From (1) we can already say,
Angle (ADC) > Angle (ABD)
Then,
AB > AC
Because we know,
Side opposite to greater angle is greater,
Then,
AB > AD
Because we already know AD = AC,
Hence proved.
AD = AC
We know,
Angles opposite to equal sides are equal,
We get,
Angle (ACD) = Angle (ADC)
Again, we know,
Angle (ADC) is an exterior angle for triangle (ABD),
Exterior angle = sum of opposite interior angles
So,
Angle(ADC) = Angle(ABD) + Angle(BAD)... (1)
From (1) we can already say,
Angle (ADC) > Angle (ABD)
Then,
AB > AC
Because we know,
Side opposite to greater angle is greater,
Then,
AB > AD
Because we already know AD = AC,
Hence proved.
Attachments:
![](https://hi-static.z-dn.net/files/ddb/7a9d2ddd2abceb0d253b3e7cc392d060.jpg)
Anonymous:
your most welcome ❤
Answered by
13
Answer:
Step-by-step explanation:
Given :
In ∆ABC ,
D i s a point on BC such that AD=AC
To show/prove :
AB > AD
Proof :
In ∆ ABC,
AD= AC
=> ∠ACD = ∠ ADC ..................... (1)
( °.° angles opposite to equal sides are equal )
Now,
for ∆ ABD,
∠ ADC is an exterior angle.
But,
We know that,
exterior angle equals to the sum of opposite interior angles
So,
∠ ADC = ∠ ABD + ∠ BAD
=> ∠ ACD = ∠ ABD + ∠ BAD ..............(2)
( °.° ∠ ADC = ∠ ACD from
1 )
Now, In ∆ ABC
∠ ACD = ∠ ABD + ∠ BAD
( from
2 )
=> ∠ ACD > ∠ ABD
( °.° ∠ ACD is sum of ∠ ABD and ∠ BAD )
=> ∠ ACB > ∠ ABC
( °.° points B and D both lies on same line )
=> AB > AC
( °.° side opposite to the greater angle is greater )
=> AB > AD
( °.° AC = AD )
Hence,
Proved
Step-by-step explanation:
Given :
In ∆ABC ,
D i s a point on BC such that AD=AC
To show/prove :
AB > AD
Proof :
In ∆ ABC,
AD= AC
=> ∠ACD = ∠ ADC ..................... (1)
( °.° angles opposite to equal sides are equal )
Now,
for ∆ ABD,
∠ ADC is an exterior angle.
But,
We know that,
exterior angle equals to the sum of opposite interior angles
So,
∠ ADC = ∠ ABD + ∠ BAD
=> ∠ ACD = ∠ ABD + ∠ BAD ..............(2)
( °.° ∠ ADC = ∠ ACD from
Now, In ∆ ABC
∠ ACD = ∠ ABD + ∠ BAD
( from
=> ∠ ACD > ∠ ABD
( °.° ∠ ACD is sum of ∠ ABD and ∠ BAD )
=> ∠ ACB > ∠ ABC
( °.° points B and D both lies on same line )
=> AB > AC
( °.° side opposite to the greater angle is greater )
=> AB > AD
( °.° AC = AD )
Hence,
Proved
Attachments:
![](https://hi-static.z-dn.net/files/d0d/43d04e5967a2cdf7eebbfaa71c8f6638.jpg)
Similar questions